Devising a method for determining the coordinates of an air object by a network of two SDR receivers - Khudov, Hennadii; Hryzo, Andrii; Oleksenko, Oleksandr; Repilo, Iurii; Lisohorskyi, Bohdan; Poliakov, Andrii; Kozhushko, Yaroslav; Melnyk, Serhii; Bilous, Oleh; Sukonko, Serhii (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of determining the coordinates of an air object. The main hypothesis of the study assumed that the use of a network of two Software-Defined Radio (SDR) receivers would make it possible to determine the coordinates of an air object. The determined coordinates could be used as preliminary target designation for the radar. A method for determining the coordinates of an air object by a network of two SDR receivers has been improved, which, unlike the known ones, involves: – using signals from the airborne systems of the air object; – using SDR receivers as network elements; – using the triangulation method for determining the coordinates of an air object. The accuracy of determining the coordinates of an air object by a network of two SDR receivers has been assessed. It was found that: – the accuracy of measuring the coordinates of an air object decreases sharply as the polar angle of observation from the middle of the base approaches 0 or π; – the smallest coordinate measurement error can be ensured when the air object is located on the traverse to the middle of the base and when the distance to the air object is close to the base size; – with small bases, the non-uniformity of the dependence of the coordinate determination error on the position of the air object relative to the SDR receivers is more pronounced than with large ones; – at a long range, the error values for small bases grow rapidly, which is primarily due to the small angle of intersection of the bearing lines; – it is advisable to place SDR receivers at a sufficiently large distance from each other (recommended value: (1–3) times the distance to the air object); – the errors of measuring the coordinates of the air object have a value of (250–350) m in a sufficiently wide range of directions; – with a decrease in the base size, the errors grow rapidly (reaching a value of more than 1000 m) when the observation angle deviates from the 90° direction